2019
DOI: 10.1097/mpg.0000000000002270
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Endoscopy Findings in Children With Accidental Exposure to Concentrated Detergent Pods

Abstract: Background: Caustic ingestion with concentrated detergent pods (CDPs) is a common problem encountered in pediatric population. There is insufficient literature about endoscopic findings in CDP ingestion and hence no current consensus or guidelines regarding the need for endoscopic evaluation. Objectives: To review cases of children with exposure to CDPs from 2010 to 2016 at a tertiary care children's hospital and to identifying the possibility of a corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
(24 reference statements)
0
5
1
Order By: Relevance
“…Our analysis, similar to the study by Settimi et al, 11 showed that both boys and girls were exposed to capsules with the same frequency. On the other hand, girls dominated in the study by Yin et al, 14 while boys predominated in the study by Singh et al 10 In our study group, only 44.74% of patients could accurately determine the capsule brand with which the child had contact. In the Williams et al's study, the capsule brand was determined in 93.4% of patients.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…Our analysis, similar to the study by Settimi et al, 11 showed that both boys and girls were exposed to capsules with the same frequency. On the other hand, girls dominated in the study by Yin et al, 14 while boys predominated in the study by Singh et al 10 In our study group, only 44.74% of patients could accurately determine the capsule brand with which the child had contact. In the Williams et al's study, the capsule brand was determined in 93.4% of patients.…”
Section: Discussioncontrasting
confidence: 56%
“…In the study of Singh et al ., it was found that endoscopic examination should be performed in patients who show abnormalities on physical examination for LDC exposure. The authors of this study stated that the presence of abnormalities in the physical examination of the oral cavity correlated with 80% probability of the presence of pathological changes in the gastrointestinal tract revealed during gastroscopy 10 . On the other hand, Smith et al .…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations